Mid-axillary transversus abdominis plane block and stress response after abdominal hysterectomy: A randomised controlled placebo trial. Issue 7 (July 2021) - Ismail, Samina; Ahmed, Aliya; Hoda, Muhammad Q.; Asghar, Samie; Habib, Aysha; Aziz, Aliya
Abstract : BACKGROUND: The hormonal response to surgical trauma can have detrimental effects on patients. Transversus abdominis plane (TAP) block, which can improve analgesia after total abdominal hysterectomy (TAH) might attenuate the peri-operative stress response. OBJECTIVE: To evaluate the ability of the TAP block to reduce stress response, opioid consumption and pain following TAH and multimodal analgesia. DESIGN: Randomised, placebo-controlled double-blind study. SETTING: The current study was conducted at a university hospital from July 2016 to September 2017. PATIENTS: Fifty patients scheduled for TAH were included. Anaesthesia and postoperative analgesia were standardised. INTERVENTION: After induction of anaesthesia, patients were allocated into two groups: ultrasound-guided bilateral mid-axillary TAP block with 20 ml of bupivacaine 0.25% (Group T) or 0.9% saline (Group C). MAIN OUTCOME MEASURES: Levels of free serum cortisol, metanephrine and normetanephrine at 60 min and 6, 12 and 24 h after surgical incision. Pain scores and opioid consumption during the first 24 h after surgery. RESULTS: There was no statistically significant difference between the median [IQR] peri-operative levels of stress hormones and pain scores between groups. Compared with baseline value 9.90 [4.2 to 23.1], free serum median cortisol levels were significantly high at 6 h in Group T, 23.6 [10.1 to 42.9] P = 0.015 and Group C 23.6 [9.9 to 46.3] P = 0.014. Only Group C showed significant elevation from the baseline median levels of plasma metanephrine at 60 min, 52.8 [33.4 to 193.2] P = 0.001, 6 h, 92.70 [2.4 to 202.6] P = 0.005 and normetanephrine at 60 min 83.44 [28.98 to 114.86] P = 0.004, 6 h 78.62 [36.6 to 162.31] P = 0.0005 and 24 h 80.96 [8.6 to 110.5] P = 0.025. Mean ± SD opioid consumption was similar in both groups: 39.60 ± 14.87 in Group T vs. 43.68 ± 14.93 in Group C ( P = 0.338). CONCLUSION: Mid-axillary TAP block does not improve stress response and analgesia in patients undergoing TAH receiving multimodal analgesia. TRAIL REGISTRATION: ClinicalTrial.gov identifier: NCT03443271.